"History can't be written without us in the center": Colonial trauma, the cartographic body, and decolonizing methodologies in urban planning. (February 2023) - Sletto, Bjørn; Novoa, Magdalena; Vasudevan, Raksha
Drawing on the concept of 'cuerpo-territorio, ' we conceptualize non-Western "other mappings" as situated and historical performances that center embodied experiences, such as the multiple and persistent traumas of coloniality, that are invisibilized in Cartesian cartographic processes. In doing so, these mappings unveil how Cartesian cartography does the traumatic work of coloniality while fostering alternative, embodied spatial imaginaries based on situated practices and visceral geographies. The article discusses three mapping projects completed at different times through distinct approaches in Venezuela, Chile, and the Dominican Republic to illuminate the pluriversality of subaltern geographies within the context of historical trauma. We suggest that the process of developing other mappings in tandem with communities constitutes decolonial methodologies that disrupt the notion of maps as traditionally understood and utilized in urban planning and development. Thus, we go beyond the tradition of participatory mapping as a technical means of visibilizing subaltern territorial claims, land-uses, and preservation practices by focusing on the potentials of other mappings to foster critical thinking, dialogue, and action.